Ехокардіографічні зміни у жінок з хронічною серцевою недостатністю залежно від індексу маси тіла - Бідзіля, Петро Петрович (My University, 2015)
Досліджено ехокардіографічні зміни у жінок з хронічною серцевою недостатністю залежно від індексу маси тіла. Встановлено, що зі збільшенням індексу маси тіла відбувається наростання ступеня дилатації аорти, лівого шлуночка та правого передсердя на фоні поглиблення концентричної гіпертрофії міокарда, кальцинозу клапанів серця та діастолічної дисфункції І типу. Спостерігається переважання чистої систолічної дисфункції серед жінок з ХСН та нормальною масою тіла, та зменшення її поширеності зі збільшенням ІМТ. Chronic heart failure (CHF) is a widespread disease of cardiovascular system its prevalence is caused with improvement of diagnostic methods simultaneously with an aging of general population. Women are the half of all patients with CHF most of them has preserved fraction of output from the left ventricle with associated diastolic dysfunction. The aim of research was the study of echocardiographic changes in women with chronic heart failure depending on body mass index. Methods: There were examined 237 women with different body mass index (BMI), in 222 was diagnosed CHF of 1–111 functional class (FC). All patients underwent calculation of BMI using Ketle formula and Dopplerechocardiographic examination. The calculations of results were carried out using the methods of parametric and nonparametric statistics depending on size and distribution of samples. Results: In women with CHF the growth of dilatation of aorta, right atrium and left ventricle take place at an increase of BMI. The maximal size of the left atrium and right ventricle were registered in the group of examined person with normal body weight. The hypertrophy of left ventricle myocardium in women with CHF progresses proportionally to an increase of BMI. In patients with CHF on the background of obesity the deeper processes of valvular calcination take place. There is a predominance of pure systolic dysfunction in women with CHF and normal body weight, and reduction in its prevalence with BMI increasing. In women with CHF with an increase of BMI takes place the deepening of diastolic dysfunction (by the type of relaxation disorder) and an increase of its prevalence. The remodeling of myocardium in women with CHF in most cases was presented by concentric hypertrophy of the left ventricle and its frequency is directly proportional to an increase of BMI.
Keywords: ехокардіографічні зміни; жінки; хронічна серцева недостатність; індекс маси тіла; echocardiographic changes; women; chronic heart failure; body mass index